Opacity effects in a solid-density aluminium plasma created by photo-excitation with an X-ray laser - Rackstraw, D; Vinko, S; Ciricosta, O; Cho, B; Engelhorn, K; Chung, H; Brown, C; Burian, T; Chalupsky, J; Falcone, R; Graves, C; Hajkova, V; et al. (2014)
The intensities within the focal spots of the output of recently developed X-ray sources based on free-electron-laser (FEL) technology are so great that atoms within the focal region can potentially absorb several photons during the few tens of femtosecond X-ray pulse. Furthermore, the duration of the FEL X-ray pulse is comparable to the Auger decay times of inner-shell holes created by the X-rays themselves. We report here how such a scenario can lead to opacity broadening of the fluorescence radiation emitted by the hot, dense plasma, which is created as a result of the X-radiation focussed onto a solid target, and in particular present calculations of the broadening of the Kα emission in a solid-density aluminium target, produced when the FEL photon energy is tuned below the Al K-edge, but is resonant with the Kα transition. © 2014 Elsevier B.V.